Age-related biological differences in children's and adolescents’ very rare tumors - Virgone, Calogero; Ben Ami, Tal; Roganovic, Jelena; Bien, Ewa; Reguerre, Yves; Ferrari, Andrea; Orbach, Daniel; Godzinski, Jan; Bisogno, Gianni; Farinha, Nuno Jorge; Bergamaschi, Luca; Alaggio, Rita; et al. (EJC Pediatric Oncology, 2023)
Very rare tumors (VRTs) in pediatric age represent many different diseases. They present an annual incidence < 2/1000,000 and correspond to about 11% of all cancers in patients aged 0–14 years. They can be roughly divided into two groups: one including tumors that are also rare in adults, and the other group includes adult-type tumors rarely encountered in children and adolescents. Although there is an obvious gap in knowledge regarding oncogenesis in pediatric cancers, there is some evidence of the involvement of various signalling pathways in the development of tumors in children and adolescents and sometimes in young adults. In addition, despite the rarity of these neoplasms, several attempts have been made to disclose the underlying mechanisms. More effort and resources have urgently to be devoted to deepening current knowledge and integrating new findings into the therapeutic approach, which nowadays relies on the treatment modalities used in adult oncology. The aim of this paper is to provide a review of the main solid VRTs occurring in both the pediatric and the adult age groups, highlighting the variability between groups in their biological and clinical course.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biological differences; Pediatric/adolescent oncology; Very rare tumors